(untitled) (Global Journal of Science Frontier Research, 2012)
The present investigation explains the homogeneity of plant life on the basis of frequency classes during 2009-2010 in Tehsil Takht-e-Nasrati, District Karak, Pakistan. The result shows that no homogeneity in the region among the phases and seasons. The value of frequency class is high (9) of class B and low in E (1) in phases 1 during spring season. In summer class C has high value (4.75) while it is low in A. (1). The value of class A is high (14.8) in winter. In phase 2 the class B has high value during spring (9.86) and summer (7.29) while the value of class A is high (8.86) in winter. In phase 3 and 4 the class B has high value throughout all season as compare to other classes. So the equation of homogeneity will be in phase 1; A < B > C > D > E., A < B < C > D < E., A < B < C < D > E.; in phase 2; A > B < C < D < E., A > B < C < D > E., A < B < C < D > E.; In Phase 3; A > B < C < D < E., A > B < C < D > E., A > B < C < D > E. and in Phase 4 ; A > B < C < D < E., A > B < C < D < E., A > B < C < D > E. in spring, summer and winter respectively. The heterogeneity of plant life shows that the area is under heavy biotic pressure owing to consumers and soil erosion.